A systematic review and qualitative synthesis of the experiences of parents of individuals living with Duchenne muscular dystrophy. Issue 8 (10th April 2023) - Donnelly, Clare M.; Quinlivan, Rosaline M.; Herron, Aaron; Graham, Christopher D.
Abstract: Purpose: Some parents of children with DMD find their role challenging, affecting quality of life. To inform support methods, we aimed to understand the lived experiences of parents and how these interact with disease progression. Materials and methods: PRISMA informed protocol development. Qualitative and mixed methods studies were included. Four databases were searched and study quality was assessed using a standardised measure. Extracted data were analysed using thematic synthesis. Results: 26 studies were included, comprising 362 parents. Seven descriptive themes were apparent: "Diagnostic Experiences", "Coping with the Caregiver Role", "Illness Trajectory and Associated Interventions", "Family Communication", "Network of Support", "Navigating Systems" and "Transition Experiences". Four analytical themes were then derived: "The Cyclical Nature of Grief", "Lifelong Expert in the Needs and Experiences of an Individual with DMD", "Navigating Deviation from Typical Life Course" and "Uncertainty as Ever Present". Conclusion: The extant evidence suggests that the experience of parenting a child with DMD is often characterised by: a cycle of grief that begins at diagnosis, which runs parallel to the development of expertise in caregiving; within this parents notice deviations from their child's and their own expected life course and adjust to the emotions and uncertainty that this can bring. IMPLICATIONS FOR REHABILITATION: Professionals should be cognisant to the complex grief process associated with DMD, which occurs from diagnosis onwards. There should be continued support for parents following bereavement. Peer support groups may also offer parents ways to maintain well-being. The necessity for parents to function effectively within an uncertain context that induces challenging emotions suggests a role for psychological therapies.